Anemia among Adolescent and Young Women in Low-and-Middle-Income Countries - Yasutake, Suzumi; He, Huan; Decker, Michele R.; Sonenstein, Freya L.; Astone, Nan M. (International Journal of Child Health and Nutrition, 2013)
Objective: Anemia is a global public health problem that affects maternal and infant mortality as well as human capital development. Yet there is not much research on anemia among young women in low-and-middle-income countries with nationally representative samples. The aim of the current research is to assess the extent of anemia in a critical age group: adolescents and young adults ages 15 to 24. Methods: The data are from 34 Demographic and Health Surveys and are used to describe the prevalence of anemia among pregnant and non-pregnant women by age, rural/urban residence, and household wealth. Anemia was assessed using the HemoCue® blood hemoglobin testing system. Findings: The prevalence of anemia among young women ranges from 15% to over 50%. This is substantially higher than 5%, which is the cutoff to identify a population where anemia is a public health problem. African countries show the highest prevalence of anemia; Benin, Ghana and Mali have over 60% anemia prevalence. Moreover, the prevalence of moderate to severe anemia is particularly high in African countries, over 20% in Ghana and Guinea. Our results show that anemia is a public health concern for adolescents and young adult females in all 34 countries we analyzed. Conclusion: The high prevalence of anemia among youth is alarming. Considering the importance of the adolescent and young adult years, when human capital development is consolidated and family formation begins, these findings call for interventions to redress the problem of anemia.